2011
DOI: 10.1175/2011bams3033.1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Wind to Reach Significant Penetration Levels of Wind Energy

Abstract: Improved weather forecasts help system operators know with greater accuracy how much variable renewable energy can be generated and how much other electric power they will need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 9 publications
2
48
0
Order By: Relevance
“…Thus, this study lays the groundwork for future investigations to compare the power output of the WFP scheme to the observed power production, which can be conducted with nacelle anemometer measurements (St. Martin et al 2017). Since mesoscale modelling is crucial in predicting power production in wind farms (Marquis et al 2011;Jiménez et al 2015;Wilczak et al 2015), comparisons of predicted and observed power output can help to identify areas for improvement in the WFP scheme in the WRF model. Moreover, accurate representation of wind farms in numerical weather prediction models is important for both simulating windenergy production and planning for energy infrastructure (Jacobson et al 2015;MacDonald et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study lays the groundwork for future investigations to compare the power output of the WFP scheme to the observed power production, which can be conducted with nacelle anemometer measurements (St. Martin et al 2017). Since mesoscale modelling is crucial in predicting power production in wind farms (Marquis et al 2011;Jiménez et al 2015;Wilczak et al 2015), comparisons of predicted and observed power output can help to identify areas for improvement in the WFP scheme in the WRF model. Moreover, accurate representation of wind farms in numerical weather prediction models is important for both simulating windenergy production and planning for energy infrastructure (Jacobson et al 2015;MacDonald et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The vertical levels are further stretched beyond the boundary layer. In past research involving the WRF WFP scheme, the selections of vertical resolution within the rotor layer include 9-18 m in , about 10-16 m in Volker et al (2015), about 15 m in Fitch et al (2012Fitch et al ( , 2013a and , about 20 m in Miller et al (2015) and Vautard et al (2014), about 22 m in Lee and Lundquist (2017), and about 40 m in Eriksson et al (2015) and Jiménez et al (2015). Moreover, the Mellor-Yamada-Nakanishi-Niino (MYNN) level 2.5 planetary boundary layer (PBL) scheme is required for the WFP in the WRF model version 3.8.1 .…”
Section: Modellingmentioning
confidence: 99%
“…In recent years, numerical weather prediction (NWP) models have become an indispensable tool in the wind-energy industry, not only in day-to-day wind-energy production forecasts , but also to support wide-scale windpower penetration (Marquis et al, 2011) and wind resource assessment. To forecast power production accurately at wind farms, the simulation tools should resolve all physical processes relevant to the wind field, including possible impacts of the wind turbines themselves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stateof-the-art load forecasts can achieve high accuracy in the day-ahead stage. In contrast to load forecasting, the variable wind generation is very difficult to be accurately predicted at 24 − 36 hours ahead, only short-term (hours ahead) prediction is of acceptable confidence; see Monteiro et al (2009) and Marquis et al (2011).…”
Section: Power System Schedulingmentioning
confidence: 99%